The Causal Relationship between Crude Oil Price, Exchange Rate and Rice Price - Adam, Pasrun; Rosnawintang, Rosnawintang; Saidi, La Ode; Tondi, La; Sani, La Ode Arsad (International Journal of Energy Economics and Policy, 2018)
This study aims to examine the causal relationship between crude oil price, IDR/EUR exchange rate, and rice price by using monthly data from January 2000 to September 2017. The result of data analysis using VAR model shows that there is no long-term relationship between crude oil price, IDR/EUR exchange rate, and the price of rice. The relationhip that happens is only in short-term one. Granger causality test result shows that the direction of relationship is from crude oil price and IDR/EUR exchange rate to rice price. The relationship between crude oil price and rice price is positive, while the relationship between IDR/EUR exchange rate and rice price is positive before the third month. However, this relationship turns into negative after the third month. Keywords: Crude oil price, exchange rate, rice price, VAR model. JEL Classifications: C58, G150, Q13, Q430